Cenários como método de prospecção aberta colaborativa para MPMEs - Lucas Silva Moreira (2020)
Changes in social, technological, cultural and organizational environments have made traditional approaches to strategy less efficient and, recently, the strategic process has been changing. Circumstances call for more appropriate ways of working, and in this context characterized by constant disruptive change and innovation, uncertainty and complexity, foresight exercises emerge as an appropriate option. Open Foresight, along the same lines as Open Innovation, has been proposed as a management practice to reduce decision-makers uncertainty about the future through the input of other companies and stakeholders. In an inter-organizational collaboration format, methods such as scenarios allow micro, small and medium-sized enterprises (MSMEs) to do strategic foresight with few resources. This research investigated the use of collaborative open foresight by MSMEs as a way to connect knowledge and experience from diverse professionals and, consequently, to reduce decision makers uncertainty about future developments and innovation strategies and to overcome the resource constraints barrier. For this, a base model of foresight scenarios was developed and applied in two real cases – the Future of Coworkings in 2025 and the Future of Labor in 2030 – with owners of coworkings and human resource managers, respectively, and the usefulness of this method was evaluated by the participants through questionnaires. The results of these assessments reinforce the idea that collaborative open foresight using the scenario method has potential to promote the benefits described by the corporative foresight literature and induce innovation strategies in MSMEs. Finally, some considerations have been shared considering that this method can be applied to companies that face a context of uncertainty and complexity and want to make better decisions and innovate.